Effects of strenuous exercise on serum myosin heavy chain fragments in male triathletes - Prou, E.; Margaritis, I.; Tessier, F.; Marini, J. F. (International Journal of Sports Medicine, 1996)
During the Nice Triathlon (June 26, 1994), the serum levels of type I myosin heavy chain (MHC) fragments and creatine kinase (CK and CK-MB) activities were assessed in 12 athletes in order to evaluate the exercise-induced muscle damage. Blood samples (BS) were taken 2 days before the event (baseline), on arrival, 6 and 24 h later, and 2 and 4 days later. The mean results (and SD) were respectively: MHC (microU.I-1): 142 (69), 156 (116), 242 (144), 1183 (574), 2603 (1405), 1002 (523); CK (U.I-1): 109 (27), 626 (267), 1188 (562), 1159 (442), 633 (385), 224 (119). The CK peak occurred at BS-6h for 8 subjects, and at BS-24h for the other ones. The MHC peak occurred at BS-48h in all the subjects. The CK-MB/CK ratios exhibited a profile similar to those described previously. Serum MHC peak values were correlated with CK ones (r = 0.67; p < 0.05). After a four-day recovery period, as the CK values had decreased, the MHC levels were still elevated. The main result of the study is the MHC peak occurrence at BS-48h in all the subjects.